### Home > CAAC > Chapter 4 > Lesson 4.1.5 > Problem 4-45

4-45.

For more help with parts (a) - (d), see the equation mat in problem 2-105.

First, try rewriting all of the subtraction as addition, then attempt to solve by simplifying like terms.

3*p* + (−7) + 9 + (−2*p*) = *p* + 2 *p* + 2 = *p* + 2 *p* = *p*

Since *p* = *p* (or 2 = 2, depending on how you solved the problem), *p* can equal any number.

One strategy is to rewrite all of the subtraction within the problem as addition.

− *y*^{2} + 2 = *y*^{2} + − 5 + −2*y*^{2}

Now simplify, starting with combining like terms and then with isolating the variable.

−*y*^{2} + 2 = −*y*^{2} + −5

2 = −5

No solution because 2 is not equal to −5.